Analisis Pengesahan Faktor (CFA) Instrumen Kajian Cinta Ilmu Dan Keperibadian Ummah Cemerlang - Nazneen Binti Ismail; Syaidatun Nazirah Abu Zahrin; Norhayati Rafida Abdul Rahim (UKM Press, 2024)
Volume: 92 No: 2